Estrategias didácticas para el fomento de la lectura comprensiva en estudiantes de tercero y cuarto año de educación básica en la unidad educativa comunitaria intercultural bilingüe Surupucyu, parroquia Guanujo, cantón Guaranda, provincia Bolívar, período académico octubre 2023 – febrero 2024 - Pullotasig Tipanluisa, Tifany Dayanna (2024)
This research report is focused on the development of didactic strategies in order to contribute to improve the comprehension reading of elementary school students. Since comprehensive reading involves understanding and making sense of any content of a text, including the selection of materials that are attractive to children. In the same way, the investigation is carried out in the intercultural bilingual community educational unit "Surupucyu", the problems that exist and the methodological strategies were applied for the development of the children's capacity, since the problem exists and it was the non-use of different didactic strategies that can help them to improve their reading comprehension, even there is a lack of interest that some students present. For this reason, the objective of this study was to make known the use of didactic strategies as methodological tools that are useful for children from early ages that allow a strengthening appropriate to their age. Several activities were carried out with the objective of improving and enriching vocabulary through workshops. These activities seek not only to strengthen academic performance but also to improve reading skills in the classroom, which contribute to improve their learning in a considered manner and to support these efforts, a descriptive field research was implemented. In the classroom, various activities were carried out to enhance the participation of all students through the introduction of stories, books and magazines. These didactic strategies have proven to be effective, as they have contributed significantly to improving students' vocabulary and reading skills. In addition, the activities implemented generated an increase in motivation within the classroom, highlighting the importance of enriching the educational environment with creative and stimulating approaches